Bulk growth and analysis on luminescence, third order nonlinear optical, laser damage threshold, dielectric and thermal properties of KDP crystal doped with BTZC complex. (10th November 2018) - Rasal, Y. B.; Anis, Mohd; Shirsat, M. D.; Hussaini, S. S.
Abstract: The 34 × 10 × 06 mm 3 bulk single crystal of bis-thiourea zinc chloride (BTZC) doped potassium dihydrogen phosphate (KDP) material has been grown from solution evaporation growth technique. The color centered photoluminescence nature of grown crystal has been investigated in visible region of interest. The He–Ne laser assisted Z-scan analysis has been carried out to explore the promising third order nonlinear optical behavior of BTZC-KDP crystal. The origin of nonlinear refraction ( n 2 ), the absorption coefficient ( β ) and susceptibility ( χ 3 ) has been discussed and their respective magnitudes have been determined using the Z-scan transmittance data. The high magnitude of laser damage threshold (GW/cm 2 ) of grown crystal has been determined using the 1064 nm Nd:YAG laser. The influence of increasing temperature on dielectric constant and dielectric loss of pure and BTZC doped KDP crystal has been comparatively investigated. The thermal decomposition and the melting profile of BTZC doped KDP crystal has been investigated by means of simultaneous thermogravimetric and differential thermal analysis.